KELENGKAPAN INFORMED CONSENT TINDAKAN BEDAH MENUNJANG AKREDITASI JCI STANDAR HPK 6 PASIEN ORTHOPEDI - Leni Herfiyanti (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2015)
AbstractInformed consent is consent given by the patient or the patient’s family on the basis of description of the medical acts to be performed on the patient. For doctors informed consent can create a sense of security, and can be used self-defense against possible claims or lawsuits from patients or their families arise when unwanted. While the patient, is a tribute to the rights of the patient and can be used as an excuse lawsuit against the doctor, in case of deviations from the medical practice mean consent given medical action. In addition Informed consent is also one important indicator in the assessment of accreditation. Purpose of this study is to determine the completeness of the data on Informed Consent Orthopaedic surgery in patients at Dr Hasan Sadikin, knowing assessment JCI Accreditation Standards Assessment HPK.6 Orthopaedic patients at Dr Hasan Sadikin and determine completeness relation Informed Consent surgery with JCI Accreditation assessment Assessment Standards HPK.6. The method used in this research is descriptive method qualitative approach. The Data collection by observation, literature reviews, and interviews. Total population and sample in this study as many as 61 medical records. The results showed the biggest omissions contained in the charging Informed Consent items Prognosis explanation by 54.1%, Alternatives & Risk by 52.5%, and complications of 50.8%. Conclusion of the influence Completeness Implementation Completion and Informed Consent of the assessment JCI Accreditation Standards Assessment HPK.6.Keyword: Completeness of Informed consent, JCI accreditation standards, Patient and Family Rights Assessment 6AbstrakInformed consent merupakan persetujuan yang diberikan oleh pasien atau keluarga pasien atas dasar penjelasan mengenai tindak medis yang akan dilakukan terhadap pasien. Bagi dokter informed consent dapat membuat rasa aman, sekaligus dapat digunakan pembela diri terhadap kemungkinan adanya tuntutan atau gugatan dari pasien atau keluarganya apabila timbul yang tidak diinginkan. Sedangkan pasien, merupakan penghargaan terhadap hak-hak oleh pasien dan dapat digunakan sebagai alasan gugatan terhadap dokter, apabila terjadi penyimpangan praktik kedokteran dari maksud diberikannya persetujuan tindakan medis. Selain itu Informed consent juga menjadi salah satu indikator penting dalam penilaian akreditasi. Tujuan Penelitian ini yaitu untuk mengetahui kelengkapan pengisian data pada Informed Consent tindakan bedah pada pasien Orthopedi di RSUP Hasan Sadikin Bandung, mengetahui penilaian Akreditasi JCI Standar Penilaian HPK.6 pada pasien Orthopedi di RSUP Hasan Sadikin Bandung serta mengetahui kaitan kelengkapan pengisian fInformed Consent tindakan bedah dengan penilaian Akreditasi JCI Standar Penilaian HPK.6. Metode penelitian yang digunakan dalam penelitian ini yaitu metode deskriptif pendekatan kualitatif. Pengumpulan data dilakukan dengan cara observasi, tinjauan pustaka, dan wawancara. Jumlah populasi dan sampel dalam penelitian ini sebanyak 61 rekam medis. Hasil penelitian menunjukkan adanya ketidaklengkapan terbesar terdapat pada pengisian Informed Consent item penjelasan Prognosis sebesar 54,1% , Alternatif & Resiko sebesar 52,5%, dan Komplikasi sebesar 50,8%. Kata Kunci : Kelengkapan Informed consent, Standar akreditasi JCI, Penilaian Hak Pasien dan Keluarga (HPK) 6.